Children's Healthcare in Soviet Russia During Soviet Famine of 1932-1933 (Following Moscow and Samara Data) - Valery Yu. Albitskiy; Stella A. Sher; Roman S. Serebryaniy; Oksana V. Yaremchuk (Вопросы современной педиатрии)
The results of historical and medical research reflecting one of the most tragic pages in the Soviet history and Stalinism era — the famine of 1932-1933 that covers several regions of the country — are presented. The aim of this research was the analysis of situation with children healthcare during the famine in the country in general and in the Middle Volga region (future Samara region) particularly. Publications of Soviet medical historians withhold the data about children’s healthcare problems during the famine of the 1930s. It has been established that the data of children mortality in national demographics of the 1930s was falsified (according to post-Soviet literary and declassified archive sources). The famine was accompanied by the increase of children morbidity and mortality due to outbreaks of highly infectious diseases (smallpox, cholera), typhus fever and typhoid fever, dysentery, childhood infections (scarlet fever, measles), septic angina, tuberculosis and malaria. If the level of infant mortality in 1932-1933 yrs could be the same as in 1928, it would be possible to save up to half a million (according to official statistical data) or even one million (according to estimated figures) children lives according to calculations of authors.